Reconceptualizing Cerebral Palsy as a Lifelong Condition Characterized by Systemic and Accelerated Biological Decline - Shannon R. Strader; Joline E. Brandenburg; Andrea A. Domenighetti (American Journal of Physical Medicine & Rehabilitation, 2026)
Cerebral palsy (CP), the most common childhood-onset disability worldwide, affects an estimated 50 million individuals globally. Although most individuals with CP are adults, CP education and training remain heavily concentrated within pediatric subspecialties, contributing to substantial gaps in adult care. At the same time, emerging evidence demonstrates that CP is associated with progressive multisystem, metabolic, musculoskeletal, and cellular changes across the lifespan, despite the original brain injury being nonprogressive. Current educational models, however, continue to frame CP primarily as a pediatric motor disorder, limiting clinician preparedness to address the complex health needs of aging adults with CP. This perspective paper argues that physiatry is uniquely positioned to lead a paradigm shift in residency education by reframing CP as a lifelong condition characterized by systemic involvement and accelerated biological aging. We propose a lifespan-oriented educational framework that integrates contemporary understanding of CP pathophysiology, multimorbidity, functional decline, and rehabilitation needs across adulthood. Expanding CP-focused education within physiatry residency training may improve clinician preparedness and represents one component of broader efforts to improve healthcare access, interdisciplinary care coordination, and long-term outcomes for adolescents and adults aging with CP.